Development of nuclear transfer goat embryos derived from in vitro matured oocytes as recipient cytoplasm and blastomeres, fetal fibroblasts and cumulus cells as nuclear donors - RAO, B S; RAO, V H (The Indian Journal of Animal Sciences, 2013)
In vitro development of goat nuclear transfer embryos produced using in vitro matured oocytes as recipient cytoplast and blastomeres, fetal fibroblast and cumulus cells as nuclear donors, was investigated. The constructed oocytes were fused and activated by electrical and chemical activation respectively. Activated nuclear transferred embryos (NTEs) were incubated overnight in tissue culture medium 199 (TCM199) +15% fetal bovine serum (FBS) at 38.5Â°C in CO2 incubator and cultured subsequently on monolayer of goat oviductal epithelial cells in TCM199+15% FBS. The fusion rates for blastomere, fibroblast and cumulus cells were 76.1, 55.7 and 57.7% respectively. The proportion of the NTEs cleaved to 2-cell were 42.2, 44.3 and 40.0% for blastomere, fibroblast and cumulus cells; respectively; 27.9, 16.3 and 12.5% of the cleaved embryos derived from blastomere, fibroblast and cumulus cell developed to blastocyst in vitro. It is concluded that the efficiency of in vitro development of goat NTEs produced from in vitro matured oocytes and blastomeres is better. However none of the recipient delivered offspring following transfer of nuclear transfer goat embryos into recipient goats.